Peran Kepala Madrasah dalam Implementasi Total Quality Management di Madrasah Tsanawiyah Negeri 5 Aceh Barat - Tihalimah Tihalimah; Farhani Farhani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this study was to determine the role of the madrasah principal in implementing TQM and to determine the strategy in maintaining a quality culture based on TQM at MTsN 5 West Aceh. This research method is descriptive qualitative. The collection techniques are observation, interviews, and documentation. The subjects of the study were the Madrasah Principal, Deputy Curriculum, Deputy Student Affairs, Treasurer, Teachers, Students, Head of Administration, and Library Manager totaling 16 people. The data analysis technique was the Miles and Huberman interactive analysis model. The results of the study obtained were: (1) the role of the madrasah principal in implementing TQM includes as an educator, as a manager, as an administrator, as a leader, and as an innovator. While the implementation of TQM that has been carried out by the madrasah principal includes: customer satisfaction, leadership, respect for everyone, and continuous improvement; (2) The Madrasah Principal's Strategy in Maintaining a Quality Culture Based on TQM includes increasing the competence of madrasah HR, creating good communication or relationships and cooperation between madrasah residents.